ASSOCIATION OF FEBRILE NEUTROPENIA WITH CHEMOTHERAPEUTIC AGENTS IN MALIGNANCIES - Swain, Byomakesh; Singh, Harpreet; Jain, Ravi; Mishra, SANDEEP (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Chemotherapy-induced febrile neutropenia (FN) is associated with substantial morbidity, mortality, and healthcare costs. The aim of this study was to evaluate episodes of FN in patients with malignancies, to find out the association of FN with various chemotherapeutic regimens, and to identify the microorganisms and the factors affecting the outcome. Methods: All patients with FN were admitted and detailed history was taken with thorough clinical evaluation. Blood, urine, and throat swab cultures and cultures from any other clinically evident site of infection were sent to all the patients. Results: Most common diagnosis was Ca breast and non-Hodgkin’s lymphoma in 13 patients. The ECOG performance status of 2 was seen in 61% of patients. The FN episodes (11%) were associated with carboplatin plus paclitaxel, and in patients with Ca cervix, Ca esophagus, and Ca ovary. The chest was involved in 16% of patients followed by the GI tract in 10%. Pseudomonas aeruginosa organism growth was seen in a 50% sample of throat swabs. The mean number of days of chemotherapy, after which patients reported to have FN, was 3.6, and median (interquartile range [IQR]) days was 2. Granulocyte colony-stimulating factor was administered in all patients in this study. The mean number of days of recovery of the patients was 4.9 and median (IQR) days was 4. Conclusion: The episodes of FN occurred mostly in patients with Ca breast, followed by non-Hodgkin’s lymphoma. FN was more commonly seen with taxanes.